Tinjauan Shopeepay Later dalam Perspektif Hukum Ekonomi Syariah: Studi Fenomenologi di Kota Bekasi - Subagja, Asep Zamzam (Prodi Ekonomi Syariah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2023)
This study aims to analyze the usage of Shopeepay Later from the perspective of Islamic economics law using a phenomenological approach. Data were obtained through a survey using a Likert scale from 51 respondents who are users of Shopeepay Later. The results of the study show that the majority of respondents have a positive view of Shopeepay Later because it is considered advantageous for installment payments without charging interest or usury. Transparency of information and payment terms also received appreciation from the users. However, there are challenges related to understanding and implementing Islamic economic principles, as well as criticisms regarding the late payment sanctions. The recommendation of this study is for Shopeepay Later to reconsider its sanction policy and explore alternative approaches that align better with Islamic economic principles, thereby supporting the development of Islamic economics and providing services that better align with users' expectations from the perspective of Islamic economics law. This study provides in-depth insights into the perspectives and experiences of users regarding Shopeepay Later in the context of Islamic economics law and its implications for the development of technology-based services.